The Quality of Vocational Teachers: teacher education, institutional roles and professional reality - Grollmann, Philipp [Verfasser] (My University, 2008)
"What are quality vocational teachers? This article analyzes the different factors exerting an influence on the professional knowledge, practices and performance of teaching staff involved in technical and vocational education and training (TVET). The international variety of vocational teacher education patterns, profiles and recruitment practices is presented. Any assessment of the quality of teachers' work, be it in theory or practice, needs to be considered against the background of the institutional environment in which they practise. Hence, some common trends of institutional change within vocational education are introduced. Most particularly here, the author focuses on the professional reality of vocational teachers as made manifest in the conjoined elements of the knowledge of teachers and professional cultures. In doing so, the author draws on some empirical exemplars. The author shows how closely teacher education and the institutional contexts are entwined in the minds of teachers as well as in professional cultures. Finally, some conclusions are drawn as to what this implies for high-quality vocational teacher education and recruitment." (Autorenreferat, BIBB-Doku)
Keywords: P 3.2.3 Lehrer; G 1.2.3.2 Anforderungen & Bedarfe; L 6 Qualität; Berufsschullehrer; Professionalisierung; Lehrerbildung; Berufsbild; Anforderungsprofil; Interkulturelle Faktoren